Advances in environmental accounting & management. Vol. 2 - Martin Freedman; Bikki Jaggi (Advances in environmental accounting & management., 2003)
The accounting profession, especially in the US, has lost credibility and this has serious implications for environmental reporting. As a number of papers in this volume attest, the amount of environmental reporting has increased in the period from the 1980s-mid 1990s. However, the value of those disclosures is open to serious question. The research for most of the papers in this volume was completed prior to the Enron scandal, but the findings indicate a need to re-evaluate what is reported about the firm's relationship to the physical environment.